Fault Lines in Corporate Governance : Directors Versus Shareholders - Hassan, Halyani (2004)
The economic downturn faced by the Asian countries in 1997 highlighted the importance of good corporate governance practices. Entailed from that crisis, measures undertaken towards improving the standard of corporate governance within the Malaysian corporate sector have been extensive. The Malaysian Code on Corporate Governance were introduced by the Malaysian Institute of Corporate Governance. The Kuala Lurnpur Stock Exchange Listing Requirements were revamped. Other rules and legislation which were already in existence were viewed afresh. But they are all subject to ambiguities which may affect a conflict-free relationship between directors and shareholders and consequently affect the standard of corporate governance. This thesis intends to emphasize the fault lines or conflicts which hinder a better relationship between directors and shareholders who are the most important organs in a corporation. The dichotomy between control and ownership which refers to directors who hold the control and shareholders who hold the ownership, has contributed to the existence of the fault lines. These fault lines are discussed in several areas of company law for instance, power to manage, refusal to register transfer of shares, winding up and general meeting. The research methodology adopted for this thesis involves judicial and legislative interpretation combined with comparative analysis from other jurisdictions with positive developments. Analysis of case law has shown the approach taken by the courts in solving conflicts between directors and shareholders. This study proposes some recommendations, for instance, amending the ambiguous provisions concerning the power to manage and to wind up corporation and expanding the concept of fiduciary duty beyond its traditional scope to apply to the shareholders in exceptional circumstances. These proposals aim at providing a balance of power between these two organs. Although corporate governance covers a wider scope than merely focusing on the directors and shareholders relationship, improving this relationship will consequently improve the standard of corporate governance. Both directors and shareholders have their own role in achieving that purpose. In the final analysis, assisted by relevant rules and regulations and their conscious conduct in improving their relationship, a better standard of corporate governance can be attained which will implicitly affect the corporate economic condition.